IN VITRO ANTIOXIDANT ACTIVITY OF VARIOUS LEAF EXTRACTS OF CANTHIUM COROMANDELICUM(BURM.F.) ALSTON. - SHABI RUSKIN R; B, VasanthaKumari; T, citarasu (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Objectives: The objective of this study was to estimate the total phenolic and flavonoid contents and to explore the antioxidant potential of various leaf extracts (chloroform, ethyl acetate, and ethanol) of Canthium coromandelicum, which is considered traditionally as an important medicinal plant. Methods: Antioxidant properties of the extracts were assessed using 1, 1- diphenyl -2- picrylhydrazyl and hydrogen peroxide radical scavenging assays for ascorbic acid equivalents. The total phenolic and flavonoid contents were also investigated to determine their correlation with the antioxidant activity of the leaf extracts and expressed in Gallic acid and quercetin equivalents, respectively. Results: The results showed that the content of total phenols and flavonoids was found to be high in ethyl acetate extract which was recorded as 61.02Â±1.30 mg Gallic acid equivalent (GAE/g) and 81.72Â±0.61 QE/g, respectively. Compared to other extracts, ethyl acetate leaf extract was found to possess high antioxidant activity at p<0.05 level, with high percentage of inhibition at 100 Î¼g/ml concentration (82.70%) toward hydrogen peroxide radical scavenging with IC50 value 62.94 Î¼g/ml. Statistically, two-tailed Pearson's correlation showed strong positive correlations between hydrogen peroxide radical scavenging activity and total phenolic contents (TPC) (r=1.000) at p<0.05 level. Conclusion: The results obtained in this study clearly signifies that the ethyl acetate leaf extract of C. coromandelicum has high content of total phenols which are correlated to its antioxidant activity and thus has the potential to use as a source of natural antioxidants and can be explored as a therapeutic agent in free radical induced diseases. Â